Employee stock options : financial reporting effects and implications (evidence from Singapore). - Loh, Eng Kiat. (2008)
This study seeks to quantify the effects of expensing ESOs on Singapore companies’ net income using the Black-Scholes option pricing model of valuation. We also examine whether an earnings management motive exist behind these grant of ESOs by adopting the award-winning methodology proposed by Matsunaga [1995].